A Review of Metal Exposure and Its Effects on Bone Health - Juliana Rodríguez; Patricia Mónica Mandalunis (Journal of Toxicology)
The presence of metals in the environment is a matter of concern, since human activities are the major cause of pollution and metals can enter the food chain and bioaccumulate in hard and soft tissues/organs, which results in a long half-life of the metal in the body. Metal intoxication has a negative impact on human health and can alter different systems depending on metal type and concentration and duration of metal exposure. The present review focuses on the most common metals found in contaminated areas (cadmium, zinc, copper, nickel, mercury, chromium, lead, aluminum, titanium, and iron, as well as metalloid arsenic) and their effects on bone tissue. Both the lack and excess of these metals in the body can alter bone dynamics. Long term exposure and short exposure to high concentrations induce an imbalance in the bone remodeling process, altering both formation and resorption and leading to the development of different bone pathologies.